A Zn azelate MOF: combining antibacterial effect. Issue 2 (11th July 2014) - Tamames-Tabar, C.; Imbuluzqueta, E.; Guillou, N.; Serre, C.; Miller, S. R.; Elkaïm, E.; Horcajada, P.; Blanco-Prieto, M. J.
Abstract : A novel biocompatible and bioactive zinc azelate metal–organic framework (BioMIL-5) was hydrothermally synthesized with interesting long-term antibacterial properties. Abstract : A novel biocompatible and bioactive Metal–Organic Framework (BioMOF), named BioMIL-5 (Bioactive Materials from Institut Lavoisier), was hydrothermally synthesized from a Zn 2+ salt and azelaic acid, both with interesting antibacterial and dermatological properties. Its structure was determined by high resolution X-ray powder diffraction, and further characterized by infrared spectroscopy, thermogravimetric analysis and elemental analysis. The determination of the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) values of BioMIL-5 in Staphylococcus aureus and Staphylococcus epidermidis demonstrated that the antimicrobial activity of the individual components of BioMIL-5 were maintained after its synthesis. Moreover, BioMIL-5 was found to be stable in water and in bacterial culture medium, especially in water, leading to the subsequent progressive release of its active constituents, AzA and Zn 2+ ions. Interestingly, this slow active delivery allowed control of the growth of a S. epidermidis suspension over 7 days. The high stability of this material and the maintenance of its antibacterial properties make BioMIL-5 a good candidate for future bioapplications, for skin care and in cosmetics.